Fertility and reproductive history of sterilized and non-sterilized women in Campinas, São Paulo, Brazil - Maria José Duarte Osis; Anibal Faúndes; Maria Helena de Sousa; Graciana Alves Duarte; Patricia Bailey
This article compares sterilized and non-sterilized women in relation to socio-demographic characteristics, reproductive history, and cohabitation status. Women from 30 to 49 years of age and residing in Campinas, São Paulo State, Brazil, were interviewed with a pre-tested and structured questionnaire: 236 women sterilized at least five years before the interview and 236 non-sterilized women. The sterilized women were significantly more likely to be married or cohabiting, to be younger when they began cohabiting, and to have been in the union longer than the non-sterilized women. They also began childbearing at an earlier age and had a history of more pregnancies and more live births than non-sterilized women. Factors associated with a history of 3 or more live births at the time of the interview were surgical sterilization, younger age at first childbirth, older age at the interview, recognition of fewer contraceptive methods, and lower per capita income. The article concludes that sterilization generally appears to be the consequence of higher fertility in a group of women who initiate childbearing early in life, although its role in preventing these women from having even larger families may also have a demographic impact.